THE COMMUNIST PARTY OF CHILE AND POLICIES ALLIANCE: POPULAR FRONT TO THE NATIONAL UNION AGAINST FASCISM, 1935-1943 - Venegas Valdebenito, Hernán (Revista de Historia Social y de las Mentalidades, 2024)
Since the mid 1930s the Chilean Communist Party defined a policy alternative to its proposal for achieving revolution in Chile, in stages and gradually. This fundamental change in the future of the organization resulted in the long term, in a series of frictions within the Chilean left during that decade. The party developed the belief that significant social change is the result of qualitative progress in a democratic process of changes implemented from state institutions. This meant the dismissel, as unworkable and risky, flows the traditional stance of the Chilean left immediate leap to a socialist revolution. This also meant the relegation of military of strategy as a route to empowerment, at least until the conditions of enlargement of the democratic sistem were mature for the masses rise to power.